RISIKO RUANG DIGITAL BAGI PEREMPUAN DI ERA KEMAJUAN TEKNOLOGI KOMUNIKASI - Klau, Stanis; Tahir, Andi; Putri, Asmarandani Heryadi (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2026)
Advances in communication technology have expanded women's participation in the digital space while simultaneously increasing their exposure to various forms of gender-based violence that threaten their security, privacy, and participation in the digital public sphere. This study aims to analyze the risks faced by women in digital spaces as a consequence of advancements in communication technology and to examine their implications for women's digital security. This study employed a qualitative approach using a literature review and Focus Group Discussion (FGD). The FGD was conducted on June 18, 2025, at SMK PGRI 1 Palimanan, Cirebon Regency, involving 30 female participants aged 17 years and above. Data were analyzed using thematic analysis through data reduction, categorization, interpretation, and conclusion drawing. The findings indicate that women encounter various digital risks, including online sexual harassment, cyberstalking, doxing, digital identity misuse, online fraud, and AI-generated manipulative content. The study also reveals that the characteristics of contemporary communication technologies, such as user anonymity, borderless connectivity, and the rapid reproducibility of digital content, increase women's vulnerability in digital environments. Furthermore, the FGD contributed to improving participants' understanding of digital security, personal data protection, and risk mitigation strategies. This study concludes that strengthening digital literacy should be integrated with gender-responsive regulations, more accountable digital platform governance, and multi-stakeholder collaboration to foster a safer, more inclusive, and sustainable digital environment for women.